Diagnostic Care Pathways in Dementia - Christine E. Wells; Sarah J. Smith (SAGE Publishing, 2017)
Objectives: Increasing diagnostic rates of dementia is a national health priority; to meet this priority, improvement needs to be made to diagnostic services. It has been increasingly recognized that primary can play a significant role in the diagnostic journey for people with dementia, with some diagnostic services entirely located in primary care. This article reviews the extent of the involvement of primary care in diagnostic care pathways for people presenting with memory complaints within England, and presents examples of innovative approaches, which may be of interest to practitioners. Method: A rapid review was undertaken to identify articles outlining diagnostic care pathways for dementia involving primary care in England. Results: Six articles relating to pathway evaluations and innovative approaches involving primary care were deemed suitable for inclusion in the review. Conclusions: The review found examples of diagnostic pathways and innovative practices being implemented in in primary care. These practices aligned to the strategic ambitions of the National Dementia Strategy. However, it was widely acknowledged that there is a need to improve postdiagnostic pathways; in particular, access to postdiagnostic support. This issue is being reflected in contemporary policy initiatives such as the Department of Health's 2016 Joint Declaration on postdiagnostic dementia care and support.